Vallecular cyst in an infant with stridor: a case report - Lageju, Nabin; Guragain, Rajendra Prasad Sharma (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Vallecular cysts are rare and generally asymptomatic. In infants and children they present with stridor, feeding difficulties, failure to thrive. Treatment is surgical excision with cautery or laser.Presentation of Case: We discuss the clinical, radiological presentation of a 7 months old child with vallecular cyst which was surgically treated with deroofing and marsupialisation with elecrocautery. There was no recurrence even up 2 years of follow-up.Discussion: Flexible nasopharyngolaryngoscopic examination was done which showed present of swelling in the left vallecula pushing the epiglottis posteriorly and to the right with narrowed normal endolarynx. Radiological investigations with CT scan showed cystic lesion noted in left side of neck with no septation and solid component. The lesion was extending to ipsilateral vallecula and paraglottic region with narrowing of endolarynx.Conclusion: Vallecular cyst is rare cause of noisy breathing in infants and children. In adults it is usually asymptomatic. Treatment of choice is marsupialization with electrocautery or laser.